T-shaped pars plana scleral incision to remove large intraocular foreign body - Toro, Mario Damiano; Nowomiejska, Katarzyna; Concilio, Marina; Motta, Lorenzo; Rekas, Krzysztof Marek; Costagliola, Ciro; Avitabile, Teresio; Castellino, Niccolò; Caputo, Georges; Choragiewicz, Tomasz; Rejdak, Robert (Frontiers in Medicine, 2024)
Aim: To investigate the efficacy and safety profile of T-shaped pars plana scleral incision technique in removing large intraocular foreign bodies, during 23-gauge pars plana vitrectomy.Retrospective interventional case series that included patients diagnosed with a large intraocular foreign body (IOFB). Possible postoperative complications were recorded 24 hours, one month, 3 and 6 months postoperatively.Results: Thirty eyes of 30 patients (48±5 years old) were enrolled. All IOFBs were successfully removed: mean diameters of 7.8±2.0 mm and 2.6±0.3 mm. Silicone oil and sulfur hexafluoride were used in 27 and 3 eyes, respectively. Lensectomy was performed in 27 eyes. Intraocular lens was implanted at first attempt in 12 eyes; during a second operation in 12 eyes and 6 eyes remained aphakic. At any follow-up, no signs of postoperative complications were observed. Secondary retinal detachment occurred in 12 eyes. Mean preoperative corrected distance visual acuity was 0.04, on the Snellen scale; it increased to 0.07, at last follow-up. Mean intraocular pressure was 17.97 mmHg. All eyes were preserved.T-shaped scleral incision could be an effective, safe and easy-to-perform standard procedure to remove large IOFBs during pars plana vitrectomy, without increasing the risk of surgical complications and additional damage to the ocular tissues.